Pengaruh Pembelajaran Bilingual Terhadap Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar (PGSD): Penelitian - Tiarnita Maria Sarjani; Sandy Despian Permana; Saiba Oktania; Nadia Fitriani Rambe; Yulia Armaini Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Bilingual learning has emerged as a significant trend in higher education, particularly within the Elementary School Teacher Education (PGSD) program. This article examines the impact of bilingual instruction on students’ academic competence, pedagogical skills, and cognitive development, drawing on language acquisition theory, recent literature, and empirical studies from the past four years. Findings indicate that bilingual practices strengthen academic communication, enhance digital literacy, and better prepare students to teach in increasingly multilingual elementary classrooms. Nevertheless, challenges such as language anxiety, cognitive load, and limited academic support remain obstacles. This study also provides recommendations for effective strategies in implementing bilingual learning within PGSD programs.